2013
DOI: 10.1002/jbm.a.34943
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale topographic changes on sterilized glass surfaces affect cell adhesion and spreading

Abstract: Producing sterile glass surfaces is of great importance for a wide range of laboratory and medical applications, including in vitro cell culture and tissue engineering. However, sterilization may change the surface properties of glass and thereby affect its use for medical applications, for instance as a substrate for culturing cells. To investigate potential effects of sterilization on glass surface topography, borosilicate glass coverslips were left untreated or subjected to several common sterilization proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
(49 reference statements)
2
6
1
Order By: Relevance
“…For surface free energy, the zirconia samples increased after sterilization treatments in all groups in our study. The result is consistent with a study by Wittenburg also revealed that steam sterilized glass exhibited significantly lower contact angle values than untreated glass samples [43]. A study by Kummer et al which found that UV irradiation on Ti could increase the formation of Ti-OH and result in the increase of surface wettability and surface energy [14].…”
Section: Discussionsupporting
confidence: 90%
“…For surface free energy, the zirconia samples increased after sterilization treatments in all groups in our study. The result is consistent with a study by Wittenburg also revealed that steam sterilized glass exhibited significantly lower contact angle values than untreated glass samples [43]. A study by Kummer et al which found that UV irradiation on Ti could increase the formation of Ti-OH and result in the increase of surface wettability and surface energy [14].…”
Section: Discussionsupporting
confidence: 90%
“…e reduction of the density of CH 3 groups compared to the hydroxyl groups has an important influence by increasing the hydrophilic behavior [17] of the sterilized hybrid coatings. Similar results were published by Wittenburg et al [36] and Han et al [37] when glass and zirconia surfaces were sterilized using similar processes. e highest contact angle values were found for the autoclaved samples, followed by the samples sterilized with ethylene oxide, and hydrogen peroxide plasma.…”
Section: Teos/mtes (24 H)supporting
confidence: 88%
“…Some opposite results have been also reported [40,41]. On the other hand, no correlation is observed between the surface hydrophilicity and cell adhesion [42,43]. In this study, the anodized E1 and E2 specimens with super hydrophilic surface (PBS contact angle <5°) revealed better HNEpC attachment, spreading, and proliferation than the nonanodized M specimens.…”
Section: Responses Of Human Nasal Epithelial Cellscontrasting
confidence: 64%